IMPLEMENTATION OF LAND TITLE CERTIFICATE REVOCATION AS A FOLLOW-UP TO COURT DECISIONS: A CASE STUDY OF MADIUN DISTRICT COURT DECISION NUMBER 30/PDT.G/2020/PN.MAD - Cahyadi, Agus (jfpublisher, 2025)
The Land Title Certificate constitutes a legal instrument in the field of land administration, issued by the Ministry of Agrarian Affairs and Spatial Planning as the formal outcome of land registration processes. While the issuance of a Land Title Certificate provides legal certainty to the holder, it does not completely preclude the emergence of future disputes. One such case involved a Request for the Revocation of Ownership Certificate No. 01/Kel. Taman, which was grounded in Madiun District Court Decision No. 30/Pdt.G/2020/PN.Mad, a ruling that had obtained permanent legal force. The revocation request was subsequently submitted to the Madiun City Land Office for further action. The procedure implemented by the Madiun City Land Office adhered to the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency No. 21 of 2020 concerning the Handling and Resolution of Land Cases. This research adopts a normative juridical approach with a statutory perspective to examine two core issues: the legal framework governing the revocation of land rights and the implementation of the Madiun District Court’s final and binding decision. The results demonstrate that the legal basis for revoking land title certificates is stipulated in the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency No. 21 of 2020 on the Handling and Resolution of Land Cases.